BIR O‘LCHOVLI STEFAN MASALASI - Jo‘rayeva , D.Sh; Yarmetova , D.I (Educational Research in Universal Sciences, 2023)
Now we will construct the simplest form of mathematical model describing phase transitions. The classic Stefan problem is a solidification and melting problem, such as the transition between ice and water. To obtain a solution to the classical Stefan problem, the heat equation must be solved. As mentioned above, it is needed to obtain a unique solution. It is called the variable “Stefan condition” and given below.